A Software Development Platform for Wearable Medical Applications. - Zhang, Ruikai; Lin, Wei (Journal of Medical Systems, 2015)
Wearable medical devices have become a leading trend in healthcare industry. Microcontrollers are computers on a chip with sufficient processing power and preferred embedded computing units in those devices. We have developed a software platform specifically for the design of the wearable medical applications with a small code footprint on the microcontrollers. It is supported by the open source real time operating system FreeRTOS and supplemented with a set of standard APIs for the architectural specific hardware interfaces on the microcontrollers for data acquisition and wireless communication. We modified the tick counter routine in FreeRTOS to include a real time soft clock. When combined with the multitasking features in the FreeRTOS, the platform offers the quick development of wearable applications and easy porting of the application code to different microprocessors. Test results have demonstrated that the application software developed using this platform are highly efficient in CPU usage while maintaining a small code foot print to accommodate the limited memory space in microcontrollers.